Dramma, tragedia, romanzo: Benjamin, Adorno e le forme della Storia - Gusman, Tancredi; Farina, Mario (Status Quaestionis, 2022)
In this essay we investigate the relationship between theatre, novel and philosophy of history in the thinking of Walter Benjamin and Theodor Adorno. The key assumption, on which the two critics and philosophers seem to agree, is that a philosophy of history is possible not as a reconstruction of the unfolding of a rational principle, but solely as a connection between aesthetic products. In certain epochs, these gather around a centre, becoming legi- ble as forms. Novel, drama and tragedy thus become not only theatrical and literary genres but, for critical thought, figures in which social and historical relations become manifest and comprehensible. Starting from this assumption, we examine the connection between theatre and novel in Benjamin and Adorno, and analyse the strategic role that these assume in their reading and diagnosis of the past and present.